100, 000 lumens to treat seasonal affective disorder: A proof of concept RCT of Bright, whole‐ROom, All‐Day (BROAD) light therapy. Issue 12 (18th August 2022) - Sandkühler, Julia F.; Brochhagen, Sarah; Rohde, Paul; Muscheidt, Rosa C.; Grömer, Teja W.; Müller, Helge; Brauner, Jan M.
Abstract: Background: Seasonal affective disorder (SAD) is common and debilitating. The standard of care includes light therapy provided by a light box; however, this treatment is restrictive and only moderately effective. Advances in LED technology enable lighting solutions that emit vastly more light than traditional light boxes. Here, we assess the feasibility of BROAD (Bright, whole‐ROom, All‐Day) light therapy and get a first estimate for its potential effectiveness. Methods: Patients were randomly assigned to a treatment for 4 weeks; either a very brightly illuminated room in their home for at least 6 h per day (BROAD light therapy) or 30 min in front of a standard 10, 000 lux SAD light box. Feasibility was assessed by monitoring recruitment, adherence, and side effects. SAD symptoms were measured at baseline and after 2 and 4 weeks, with the Hamilton Depression Rating Scale‐Seasonal Affective Disorders 29‐items, self‐report version. Results: All 62 patients who started treatment were available at 4‐week follow‐up and no significant adverse effects were reported. SAD symptoms of both groups improved similarly and considerably, in line with previous results. Exploratory analyses indicate that a higher illuminance (lux) is associated with a larger symptom improvement in the BROAD light therapy group. Conclusions: BROAD light therapy is feasible and seems similarly effective as the standard of care while not confining the participants to 30 min in front of a light box. In follow‐up trials, BROAD light therapy could be modified for increased illuminance, which would likely improve its effectiveness.